Bamboo in the brain: Impalement injury over orbito-cranial region via superior orbital fissure - Pokhrel, Bibesh; Thapa, Amit (Nepal Journal of Neuroscience, 2021)
Intracranial wooden foreign bodies due to transorbital penetrating injury sparing orbital globe are relatively rare with no reported cases till date. A multidisciplinary approach with multiple imaging modalities is needed for preoperative surgical planning.In this case report, we report a case of 3-year-old male who presented to our emergency department with history of fall from 5 feet with no vision over right eye. ~2cm cut injury with sutures in situ was present over nasal ridge with pus discharge. CT scan head showed foreign body over temporal region. Right fronto-temporo-orbito-zygomatic craniotomy with removal of foreign body was done. Deep seated abscess seen over temporal fossa was evacuated and post-operatively intravenous antibiotics was continued. Contrast enhanced CT repeated on 15th post-operative day showed no remaining abscess or foreign body. The patient was discharged on oral antibiotics. The wound healed completely with no improvement of vision in 1-week follow-up.Keywords: brain abscess, orbito-cranial penetrating injury, wooden foreign body